PANDOWO LIMO PEOPLE'S CLAIM TO LAND RIGHTS (A STUDY ON PT. PERKEBUNAN NUSANTARA IV KEBUNAN BALIMBINGAN) - Ahmad Bayu Sulistyo; Lilawati Ginting (Inspiring Law Journal, 2026)
The Right to Use Business (HGU) often causes conflicts between rights holders who obtain formal legality from the state and communities who claim land based on historical control or customary rights. Such as the dispute between PT Perkebunan Nusantara IV Kebun Balimbingan and the Pandowo Limo Community in Simalungun Regency. The issues raised by the legal status of the HGU land owned by PTPN IV based on land law in Indonesia, the legal basis used by the Pandowo Limo community in claiming HGU land as their property, and the mechanism for resolving land disputes in the conflict between PTPN IV Kebun Balimbingan and the Pandowo Limo communityThe research method used is empirical legal research, which is research that examines the implementation and implementation of normative legal provisions in action in legal events that occur in society. This research is descriptive with a legislative approach to obtain a comprehensive normative and empirical understanding.The results of the study show that the legal position of the Right to Use Business (HGU) owned by PT Perkebunan Nusantara IV Kebun Balimbingan is valid and has legal force based on the Basic Agrarian Law and is evidenced by the valid HGU certificate. The claims of the Pandowo Limo people are based on hereditary control and historical legitimacy, but in the trial process they are not supported by written evidence that is strong enough according to positive law. Dispute resolution is carried out through litigation until Decision Number 19/Pdt.G/2023/PN. Sim and appeal decision Number 602/Pdt./2023/PT. MDN affirms the legal standing of PTPN IV as a legitimate right holder. This study also found that there is an inequality between administrative legality and social legitimacy, which is influenced by historical factors, weaknesses in land administration, and limited access to community law, thus reflecting the complexity of agrarian conflicts in Indonesia.